2013
DOI: 10.1080/00221686.2013.818586
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent non-uniform flows in straight compound open-channels

Abstract: The reported experimental study assesses the effects of flow non-uniformity on the momentum flux in straight compound channels. Two flumes were used, featuring vertical and sloping banks. Starting with uniform flow condition, various imbalances in the upstream discharge distribution were introduced. This resulted in a time-averaged lateral flow and advective transport of momentum, which interacted with the shear-layer turbulence generated by the compound geometry. To investigate this interaction, the three con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…We use depth‐averaged values as commonly done for uniform flows [ Shiono and Knight , ]. The depth‐averaged and time‐averaged transverse exchange of streamwise momentum has three contributions [ Proust et al ., ]: true1htrue0hρuvdz¯=ρtrue(uvtrue)true¯dρUdVdρ[U(VVd)]d where h is local flow depth and ρ is fluid density. The first contribution is the depth‐averaged Reynolds‐stress, the term ρUdVd is the momentum transfer by the transverse flow, and the term ρ[U(VVd)]d is the depth‐averaged momentum transfer by the secondary currents.…”
Section: Effect Of the Three Forcingsmentioning
confidence: 99%
See 2 more Smart Citations
“…We use depth‐averaged values as commonly done for uniform flows [ Shiono and Knight , ]. The depth‐averaged and time‐averaged transverse exchange of streamwise momentum has three contributions [ Proust et al ., ]: true1htrue0hρuvdz¯=ρtrue(uvtrue)true¯dρUdVdρ[U(VVd)]d where h is local flow depth and ρ is fluid density. The first contribution is the depth‐averaged Reynolds‐stress, the term ρUdVd is the momentum transfer by the transverse flow, and the term ρ[U(VVd)]d is the depth‐averaged momentum transfer by the secondary currents.…”
Section: Effect Of the Three Forcingsmentioning
confidence: 99%
“…Starting with uniform flow conditions, nonuniform flows are generated by imposing an imbalance in the upstream discharge distribution between subsections, keeping the total discharge constant. From a practical point of view, the study of unbalanced inflow conditions is interesting, because the velocity distribution is necessarily out of equilibrium at the upstream boundary of a compound reach [ Proust et al ., ]. For instance, an excess in FP inflow can be caused by narrowing FPs upstream of the studied reach [ Bousmar et al ., ], or by an abrupt FP contraction [ Proust et al ., ] in which a 34% flow excess was measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The position of y IP is (2013), we do not detect a lateral displacement of y IP when mass is transferred from the floodplain to the main channel. This may be due to weaker mass transfers than in the experiments of Proust et al (2013) and Peltier et al (2013). Figure 8a shows the position y U0 relative to the position y int for all test cases.…”
Section: Mixing Layer Centrementioning
confidence: 99%
“…These studies showed that the lateral momentum exchange between the main channel flow and the floodplain flow is driven by both the turbulent diffusion related to the mixing layer that forms at the main channel/floodplain interface and by the net lateral mass transfers between main channel and floodplain. Proust et al (2013) investigated the relaxation of flows in a straight smooth compound channel in which the upstream discharge distribution between main channel and floodplain was destabilized with regards to the uniform discharge distribution. It appears that the relaxation to uniformity is a relatively slow process: for an excess or a deficit in floodplain discharge of ± 19% at the flume inlet, the uniform discharge distribution is not reached 10 m downstream.…”
Section: Introductionmentioning
confidence: 99%